Economic Resilience and Modern Livelihoods: A Multidisciplinary Study of Islamic Family Law and Sharia Economics - Siti Sahnia Mammenasa Daeng Yusuf; Akbarizan Akbarizan; Nurcahaya Nurcahaya (JURNAL ISLAM NUSANTARA, 2025)
This study aims to analyse the concept of economic resilience of Muslim families from an Islamic perspective by emphasising the integration of sharia maqashid principles and the collaborative role of husband and wife in facing modern economic challenges, especially in the era of digital transformation. The study also aims to identify relevant family economic strategies based on spiritual values and Islamic ethics to strengthen family well-being and stability. The research method is a qualitative, descriptive approach, based on an in-depth literature review of journals, books, and regulations related to family law and sharia economics. The results of the study show that the family's economic resilience depends not only on financial income but also on the strength of faith, effective communication, transparent financial management, and commitment to the principles of mashlahah, justice (adl), and balance (tawazun). Economic collaboration between husband and wife has proven to be a strategic factor in strengthening household stability. The implications of this research are theoretical and practical: enriching the literature on family resilience in a sharia perspective and providing recommendations for policy development, sharia financial education, and family development to create a family of sakinah, mawaddah, and rahmah.